Synthesis of Al2TiO5 and its effect on the properties of chitosan-NH4SCN polymer electrolytes - Kufian, M.Z.; Majid, Siti Rohana; Hassan, F.; Woo, H.J.; Aziz, N.A. (Springer Verlag (Germany), 2013)
In this paper, Al2TiO5 ceramic material has been synthesised and used as filler in polymer electrolyte system to enhance the conductivity. The precursor sintered at 1,050 A degrees C and contained 0.08 mole of aluminium nitrate gives the best and complete formation of Al2TiO5. Composite polymer electrolytes of chitosan-NH4SCN containing different amount of home-made Al2TiO5 were prepared by solution casting. The addition of filler has enhanced the conductivity of polymer electrolyte. The sample 57 wt% chitosan-38 wt% NH4SCN-5 wt% Al2TiO5 exhibited the highest electrical conductivity of 2.10 x 10(-4) S cm(-1) at room temperature. The presence of the Al2TiO5 creates favourable pathways for ionic conduction through Lewis acid-base type interactions between ionic species and O/OH surface groups on alumina filler grains. In addition, the space charge region created by the presence of Al3+ could attract SCN-1 ions, thus immobilise it and increase the transport number of the cation. Degree of crystallinity is calculated from the deconvoluted X-ray diffraction patterns and it shows that the lowest degree of crystallinity is achieved when 5 wt% of filler is added. In Fourier transform infrared study, the carboxamide band of the polymer is observed to shift to higher wave number from 1,629 to 1,634 cm(-1), confirming the formation of chitosan-NH4SCN-Al2TiO5 complexes. The morphology of composite polymer electrolyte has been studied using scanning electron microscopy at room temperature.